2013
DOI: 10.1016/j.jadohealth.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Obesity and School Absenteeism Attributed to Illness or Injury Among Adolescents in the United States, 2009

Abstract: Purpose-School attendance can impact academic performance. Childhood obesity-related physical and psychosocial consequences are potentially associated with school absenteeism. Thus, we examined the association between school absenteeism attributed to illness or injury and obesity among adolescents aged 12-17 years.Methods-We used a weighted sample of 3,470 U.S. adolescents from the 2009 National Health Interview Survey. School absenteeism was measured from the parent-reported number of sick days taken in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Several explanations have been suggested for the negative association between BMI and academic performance. These include higher rates of healthrelated school absenteeism (25), reduced cognitive function (26), negative impact on self-esteem (9), concurrent depressive symptoms (8), and finally, peer and teacher prejudice (14,18). However, such a negative association was shown in previous studies to be independent of depressive symptoms, intelligence quotient (IQ) and several sociodemographic characteristics (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations have been suggested for the negative association between BMI and academic performance. These include higher rates of healthrelated school absenteeism (25), reduced cognitive function (26), negative impact on self-esteem (9), concurrent depressive symptoms (8), and finally, peer and teacher prejudice (14,18). However, such a negative association was shown in previous studies to be independent of depressive symptoms, intelligence quotient (IQ) and several sociodemographic characteristics (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies examining the relationship between children’s subjective health status and academic achievement have consistently found that poorer health status is associated with worse academic achievement outcomes. 3,4 When children are unhealthy, they may have more difficulty learning than their healthy counterparts and have poorer academic achievement outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from the US examined more than 165,000 students in grades 1–12 and found only weak associations between obesity and increased school absences [7]. A national survey in the US of 3470 adolescents reported overweight and obese pupils aged 12–17 years of having 36 and 37% more sick days, respectively, than their normal-weight peers [8]. Among 1387 US children (6–11 years) and 2185 adolescents (12–18 years) a relationship between severe absenteeism and weight status was found only in children but not adolescents [9].…”
Section: Introductionmentioning
confidence: 99%